2009
DOI: 10.34101/actaagrar/36/2789
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alveohraph and extensigraph properties of winter wheat samples

Abstract: The rheological properties of dough are determined by the amount and proportion of gliadin and glutenin proteins. Extensibility and resistance to the extension of doughs which can be measured using the extensigraph or alveograph allow good assesment of the baking behavior under realistic conditions. In our study, we compared the extensigraph and alveograph parameters of 87 flour samples. The results showed that the alveograph parameters were different from the extensigraph parameters. The classification of whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The extensograph has proved useful in the classification and assessment of flours on the basis of physical dough properties (in particular, flour strength) for both quality control and applied and basic research application (Boros et al, 2009;Dizlek & Ozer, 2017a). In the study of Iancu, Ognean, Haubelt, and Jȃşcanu (2010), the Brabender extensograph and Haubelt Flourgraph E7 were compared and they demonstrated that the equipment used can give values that similarly characterize the behavior of dough, if the same method of determination is used.…”
Section: Rheological Properties By Flourgraphmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensograph has proved useful in the classification and assessment of flours on the basis of physical dough properties (in particular, flour strength) for both quality control and applied and basic research application (Boros et al, 2009;Dizlek & Ozer, 2017a). In the study of Iancu, Ognean, Haubelt, and Jȃşcanu (2010), the Brabender extensograph and Haubelt Flourgraph E7 were compared and they demonstrated that the equipment used can give values that similarly characterize the behavior of dough, if the same method of determination is used.…”
Section: Rheological Properties By Flourgraphmentioning
confidence: 99%
“…The genotopic effect and the environmental conditions such as climate and soil and growing techniques have crucial effects on the physical, chemical and technological properties of wheat that make up quality (Barutcular et al, 2016;Otteson, Merqoum, & Ransom, 2008;Peterson, Graybosch, Baenziger, & Grombacher, 1992). There are numerous studies on bread wheat varieties and their properties (Aydoğan et al, 2013;Boros, Tarján, Mars, Borbély, & Győri, 2009;Çağlar, Karaoğlu, Bulut, Kotancılar, & Öztürk, 2011;Çağlar, Öztürk, & Bulut, S., 2006;Channa, Ghangro, Sheikh, & Nizamani, 2015;Dizlek & Ozer, 2016, 2017bÜnal, Olçay, & Özer, 1996). As wheat varieties used in flat type of bread are different from bread wheat varieties generally used, there is a limited number of studies about wheat varieties used in flat type bread.…”
Section: Introductionmentioning
confidence: 99%
“…The alveograph is accepted as one of the important tests in the assessment of the quality characteristics of wheat flour and it has previously been used in various countries (Khattak et al, 1974;Bettge et al, 1989;Indrani et al, 2007;Boros et al, 2009;Codina et al, 2011;Mironeasa and Codina, 2013). It was also suggested for breeding studies in Turkey (Kaya and Şahin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, flour used in bread making is obtained by milling of many bread wheat varieties like Tosunbey, Seval, Eser, Kenanbey, Gün 91, İkizce 96, Bayraktar 2000, Demir 2000, Zencirci 2002. There are numerous studies on bread wheat varieties and their properties (Aydoğan et al, 2012;, Boros et al, 2009, Boz et al, 2012, Channa et al, 2015, Çağlar et al, 2011, Dikici et al, 2006, Ercan and Seçkin, 1989, Mirahmetoğlu et al, 2007, Ünal et al, 1996. However, there is a limited number of studies for flour used in Gaziantep pita bread (Pekmez, 2018).…”
Section: Introductionmentioning
confidence: 99%